Evaluation of Antibody Production against Newcastle Disease Virus after Immunization with Different Vaccines in Fayoumi Chicks - Barua, Ahama Ranjan; Amin, M Mansurul; Islam, Shaiful; Chowdhury, Sukanta; Khan, M Shafiqul Islam; Asgar, M Ali (Bangladesh Journal of Microbiology, 2010)
The research work was performed in the experimental sheds and virology laboratory of the Department of Microbiology and Hygiene, Faculty of Veterinary Science, Bangladesh Agricultural University (BAU), Mymensingh during the period from January to November 2006 for the detection of persistence of maternallyderived antibody (MDA) against Newcastle disease virus (NDV) in Fayoumi chicks as well as evaluation of antibody production in chicks after vaccination. Five experimental groups of 110-day-old Fayoumi chicks were vaccinated for comparative study. Group A was vaccinated with baby chick ranikhet disease vaccine (BCRDV, F-strain), group B with Izovac B1 Hitchner® (B1 strain), group C with Cevac New L® (LaSota strain) and group D with Avinew® (VG/GA strain) through intraocular (i/o) route while group E was kept as unvaccinated control. Serum samples obtained from 10 randomly selected birds from each group on the occasion of 7, 13, 15, 17, 19 and 21 days post-vaccination (DPV) were subjected to haemagglutination inhibition (HI) test. It was found that persistence of MDA against Newcastle disease virus (NDV) retained until the age of day 20 in Fayoumi chicks and among the four commercial vaccines, Avinew® (VG/GA strain) appeared to be slightly superior compared to those of BCRDV (F-strain), Izovac B1 Hitchner® (B1 strain) and Cevac New L® (LaSota strain) in respect of HI antibody response. The F-values of HI titre among four vaccines were significantly different (p <0.01). Keywords: Newcastle disease virus (NDV); Fayoumi chicks; Maternally-derived antibody (MDA); Haemagglutination inhibition (HI); Newcastle disease (ND) vaccines DOI: http://dx.doi.org/10.3329/bjm.v25i1.4852 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 31-35